Pengembangan UMKM melalui Pendataan Lengkap Koperasi Usaha Mikro Kecil dan Menengah Kabupaten Bekasi - Yahya, Adibah; Permana, Indra; Andriyani, Meli; Zhafira, Nisa; Tsabitah, Sahlaa (Institut Ilmu Sosial dan Manajemen Stiami, 2025)
The Ministry of Cooperatives and Micro, Small and Medium Enterprises (KUMKM) conducts data collection to collect accurate and integrated data to formulate more effective policies in protecting and empowering MSMEs. The data collection target in 2024 includes 4 million data from five provinces, with Bekasi District targeting 100,000 data. To ensure broad participation, this activity involves various parties, including practitioners, academics, and communities. The data collection aims to address issues faced by MSMEs, such as lack of accurate data, access to financing, and training support. Through systematic methods, including the formation of teams and the use of mobile applications for data collection, it is hoped that this data collection can increase the economic potential of MSMEs and positively contribute to the local economy. The results of this activity show that collaboration between government, academia, and the community can improve the effectiveness of MSME development in Bekasi District. The results of this activity also showed an exceeding of the data collection target by 100.08%.